تخلیق انسانی اور اس کے مراحل سے متعلق قرآنی بیانات کی سائنسی تعبیرات: Scientific interpretations of Qur’ānic Statements on Human Creation and its Stages (Al-Qamar, 2019)
In addition to scientific theories about human creation and evolution, religious texts contain a wealth of information in this regard. As far as the Quran is concerned, it has also referred to it in various places. This article aims to study the scientific interpretation of the Qur’ānic statements about human creation and its stages. This study brings to fore the scientific interpretations of the various Qur’ānic verses in the context under consideration from various Qur’ānic commentaries.  It finds that the Qur’ānic statements about human creation and its evolution in the womb of the mother are consistent with modern science.
Keywords: Human; creation; Quran; interpretations; Science